Contact zone of slow worms Anguis fragilis Linnaeus, 1758 and Anguis colchica (Nordmann, 1840) in Poland - Grzegorz Skórzewski; Bartosz Borczyk; Stanisław Bury; Daniel Kulik; Jan Kotusz (PeerJ)
Background Legless lizards, the slow worms of the genus Anguis, are forming secondary contact zones within their Europe-wide distribution. Methods We examined 35 populations of A. fragilis and A. colchica to identify the level of morphological and genetic divergence in Poland. We applied a conventional study approach using metric, meristic, and categorial (coloration) features for a phenotype analysis, and two standard molecular markers, a mitochondrial (NADH-ubiquinone oxidoreductase chain 2; ND2) and a nuclear (V(D)J recombination-activating protein 1; RAG1) one. Results We found clear differences between A. fragilis and A. colchica in molecular markers and phenotype—in meristic features, e.g., ear opening, number of scales rows around the body, and higher than so far known diversity in ND2 and RAG1 haplotypes. The presence of five hybrids was detected in three populations in the Polish part of the European contact zone. In all hybrids, homozygous alleles of RAG1 were detected, which suggests a back-crossing within the genus. Conclusions The ability to produce fertile offspring by A. fragilis x A. colchica hybrids shows inefficient mechanisms of reproductive isolation of the two legless lizards. The hybrids were indistinguishable from parental species in head proportions (principal components and discriminant analyses) but more resembling A. colchica in meristic traits.